(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2022)
The purpose of this abstract is to offer a high-level summary of the causes, trends, andconsequences of foreign direct investments effect on India’s economic development. Increased capitalformation, technical progress, job creation, and productivity growth are all outcomes of India’s success inattracting foreign direct investment (FDI). India’s infrastructure and technological prowess have greatlyimproved thanks to foreign direct investment. Foreign direct investment (FDI) has also helped India’semployment market expand. Moreover, FDI has benefited domestic businesses via positive spillovereffects. Foreign direct investment (FDI) in India has opportunities, but there are also concerns thatshould not be disregarded. Foreign direct investment has been a key driver of development in India’seconomy. Increased industrial growth, more jobs, higher productivity, and greater competitiveness areonly some of the benefits of increased access to foreign money, technology, and knowledge.